Efficient Rehabilitation Training through MRAC Adaptive Control: A Study on Lower Limb Exoskeleton - Mustapha Amine, Sadi; Annisa, Jamali; Muhammad Asif, Zulkifli (2025)
Wearable robots for rehabilitation have significantly advanced the medical field, aiding patients with lower limb impairments in regaining mobility and enhancing their range of motion (ROM). However, optimizing control mechanisms for these robots remains challenging due to the traditional control methods' inability to adapt to the diverse needs of patients and the complexities of human gait patterns, thus limiting the effectiveness of ROM training. This study addresses these challenges by developing and evaluating a Model Reference Adaptive Control (MRAC) system for lower limb rehabilitation robots. By leveraging MRAC's adaptive capabilities, the research aims to improve the adaptability and efficiency of ROM training, thereby providing a more effective rehabilitation experience. The performance of the MRAC controller is compared with that of a traditional Proportional- Integral-Derivative (PID) controller to demonstrate the advantages and potential improvements offered by the adaptive control approach. This research contributes to the field of wearable robotics by proposing and assessing an innovative MRAC control strategy. The integration and comparative evaluation of MRAC and PID controllers seek to overcome existing limitations in ROM training, offering a more adaptive and efficient rehabilitation solution. The study's outcomes are anticipated to pave the way for future advancements in rehabilitation technology, ultimately improving the quality of life for individuals with lower limb impairments.